“Akzhayik” biosphere reserve – dynamics of change since 1980, modern condition, main risks and threats (Eurasian Journal of Ecology, 2019)
The aim of the study was to analyze the current state of the main types of ecosystems of the Akzhayykbiosphere reserve based on field geobotanical and soil work in the surveyed territory, a retrospectiveanalysis of climatic changes in the region over the past 38 years, the long-term dynamics of the hydrological parameters of the Zhayik (Ural) river, level and nature fluctuations and consequences for biotaof overtaking phenomena on the northern coast of the Caspian Sea, the study of multi-temporal satelliteimages using remote sensing methods and GIS-technology. As a result, the periodic nature of changes inregional climatic data and hydrological parameters of the Zhayik (Ural) River, as well as the Caspian Seawas revealed. It is shown that climate change trends are expressed in a decrease in the average annualrainfall and a pronounced increase in the average annual air temperature, which entails consequencesof an absolutely negative character for the Akzhayik reserve, taking into account the conditions of thearid zone in which it is located. Against the background of long-term fluctuations, a trend of a decreasein the water content of the Zhaiyk (Ural) River is revealed and a decrease in the level of the Caspian Seaoccurs, which leads to a decrease in intrazonal meso- and hydromorphic ecosystems and a decrease inbiodiversity. The effectiveness of monitoring the status of biogeocenoses of the project area based onremote sensing methods and GIS technologies is shown.Key words: Akzhaiyk biosphere reserve, hydrology, climate, Earth remote sensing methods, mapping, GIS technologies, Ural (Zhayik) river, anthropogenic transformation, ecosystem degradation.